2018
DOI: 10.1002/adfm.201800173
|View full text |Cite|
|
Sign up to set email alerts
|

Targeted Nanoparticle‐Mediated Gene Therapy Mimics Oncolytic Virus for Effective Melanoma Treatment

Abstract: Oncolytic virus has potential applications in cancer therapy. However, its clinical application is restricted by the virus‐associated biosafety issues. Here, inspired by the key role of vesicular stomatitis virus matrix protein (VSVMP) in the oncolytic vesicular stomatitis virus (VSV) induced apoptosis, a targeted nanoparticle‐delivered neutral VSVMP gene formulation is designed to act like the VSV for cancer therapy. This VSVMP formulation consists of a CRGDKGPDC peptide modified hybrid monomethoxy poly (ethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…iDPP was prepared by the previously described method. 30 To prepare the iDPP/DNA nanocomplex, we mixed the iDPP nanoparticle with plasmid DNA at a mass ratio of 25:1 by gentle pipetting and then incubated at room temperature for 30 min. Particle size and zeta potential of the nanocomplex were determined by a dynamic light scattering detector (Malvern Nano-ZS90, UK) with a 2 min of equilibration time at 25 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…iDPP was prepared by the previously described method. 30 To prepare the iDPP/DNA nanocomplex, we mixed the iDPP nanoparticle with plasmid DNA at a mass ratio of 25:1 by gentle pipetting and then incubated at room temperature for 30 min. Particle size and zeta potential of the nanocomplex were determined by a dynamic light scattering detector (Malvern Nano-ZS90, UK) with a 2 min of equilibration time at 25 °C.…”
Section: Methodsmentioning
confidence: 99%
“… 29 In our previous work, we developed an iDPP gene delivery system that could selectively deliver the DNAs into the tumor cells after intravenous administration. 30 This platform could provide a tool for intracellular expression of a peptide discovered through structure-guided drug design.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this obstacle, non-cationic nanocarriers for safe and effective gene delivery should be explored. Our previous studies have demonstrated that the biodegradable nanoparticles (iDPP), which were prepared by self-assembly of a tumor-targeted peptide (C18-PEG-iRGD), monomethoxy poly(ethlene glycol)-poly(D,L-lactide) (mPEG-PLA), and N-[1-(2,3-dioleoyloxy) propyl]-N,N,N-trimethylammonium chloride (DOTAP), could safely and efficiently deliver genes into melanoma cells 30…”
Section: Introductionmentioning
confidence: 99%
“…The resulting virus‐mimetic nanocomplex can effectively express VSVMP into ovarian cancer cells and ultimately inhibit intraperitoneal metastatic ovarian cancer. In another study, Luo et al (2018) loaded plasmids encoding VSVMP into tumor‐targeting peptide (C18‐PEG‐iRGD)‐modified neutral nanovectors. The resulting virus‐mimetic nanoparticles could be specifically taken up by melanoma cells and express VSVMP intracellularly, exhibiting effective targeting and inhibition of melanoma.…”
Section: Virus‐mimetic Systems For Tumor Therapymentioning
confidence: 99%